Aplikasi Kriptografi dan Steganografi Menggunakan Metode Least Significant Bit (LSB) dan One Time Pad (OTP) - Mahmudi, Ali; Mantja, Sandy Nataly; Rozikin, Achmad (MATICS, 2016)
Â With the development of technology, especially in the IT field, the more developed also the current exchange of information using internet technology. Security of information transmitted via the Internet network is a must to maintain the confidentiality and originality of the information. Technology to maintain the security of the information used in this paper is a cryptography and steganography. Application cryptography to secure information on the text, then the information is hidden in digital images. So that only users who have a lock / unlock passwords only, can read the message in greeting such information.